Laboratory Characteristics of Paratyphoid B Vaccines Tested in Controlled Field Trials - Hejfec, L. B. (1969)
The immunization of human beings with paratyphoid B vaccines, in doses producing a marked protective effect in field trials, resulted in H-agglutinin titers that were significantly higher than those produced by ineffective doses. In immunization of rabbits and white mice, the same difference in doses had a significant effect on the ability of vaccines to stimulate the formation of H and O antibodies. A parallel was noted between the effectiveness of vaccine for human beings and the activity of sera of the corresponding group of people in the passive mouse-protection test, with a correlation between such activity of sera and the 19S O-hemagglutinin titers. The data obtained suggested as promising the determination of agglutinin dynamics in the sera of inoculated human beings and animals to evaluate the antigenic activity of paratyphoid B vaccines in the laboratory. The passive mouse-protection test with human sera holds promise for laboratory evaluation of the effectiveness of paratyphoid B vaccines. At the same time, none of the variation of the active mouse-protection test employed permitted a significant difference to be detected between the vaccines effective and ineffective for man. Comparison of data on the frequency and degree of febrile vaccine reactions in man with results of laboratory evaluation of vaccine toxicity showed that, provided a reference vaccine with known pyrogenic capacity for man was employed, the study of stress effect of vaccines on guinea-pigs (determination of 17-oxycorticosteroid content) may permit prediction of the reactive power of the vaccine. No correlation was found between the pyrogenic capacity of vaccines for man and their toxicity for mice.